Reasoning about strategies and rational play in dynamic games - Giacomo Bonanno (University of California, Department of Economics, 2011)
We discuss a number of conceptual issues that arise in attempting to capture, in dynamic games, the notion that there is common understanding among the players that they are all rational.
Keywords: 330; belief revision; common belief; counterfactual; dynamic game; model of a game; rationality